TRANSPLACENTAL HEPATO-CURATIVE POTENTIAL OF GARLIC AGAINST SODIUM ARSENATE INDUCED OXIDATIVE STRESS IN MICE - S. Andleeb; N. Aslam; M. Habib; H. Zaman; S. Rehman; M. Imran; Z. Abbas2 (Journal of Animal and Plant Sciences, 2020)
Inorganic arsenic is a well-known toxicant and carcinogen. Millions of people in world are being affected by arsenic mainly through drinking water. Objectives: To evaluate toxic effects of sodium arsenate (Na3 AsO4) and assess protective role of garlic (Allium sativum) in minimizing its toxicological effects. Methodology: In this study, 20 pregnant female mice were divided into 4 groups. Group I (Control) was healthy control and Group II (Dose group) was orally administered with 50mg/kg of Na3 AsO4 on the “Gestation day 6” for consecutive 6 days. Group III (Dose+ Antidote group) mice were administered with 50mg/kg of Na3 AsO4 and garlic extract (30mg/kg) with a gap of one hour. Group IV (Antidote Group) was administered orally with garlic extract (30mg/kg). Results: Pregnant female mice were sacrificed at 18th day of gestation, Na3 AsO4 affected weight, limbs, and size of the fetus. It also caused pyknosis, necrosis and increased sinusoidal space, fibrosis in both mother and fetal liver of mice. High mortality rate and pregnancies loss were observed in Group II. On the other hand, garlic showed strong antioxidant activity which neutralized oxidative stress condition in both mother and fetal liver of mice in Group III. Conclusion: Our findings indicated that Na3 AsO4 is a potential toxic metalloid that can cross placenta and garlic is equally effective in ameliorating these toxicities in mice.
Keywords: Allium sativa; Nrf2 signaling pathway; mice; Mus musculus